Wonders of the solar system - Cox, Brian (British Broadcasting Corporation, 2010)
Contents: Disc. 1: Empire of the sun (The first episode illustrates how the formation and behavior of the Sun affects each planet in the Solar System. During this episode, Cox visits India to view and explain the workings of a total solar eclipse. The Auroa Borealis is also seen in Norway and an explanation of the power of the Sun occurs in death Valley, California, USA) 2. Order out of chaos (Brian Cox starts the episode in Al-Qayrawan, Tunisia to analyse the orbit of the planets around our Sun, with details on how the tilt of the earth creates the seasons. He also visits the Atlas Mountain and provides an explanation of how we see the orbit of Mars. This episode also provides an insight on the rings of Saturn and the geysers of Enceladus, including images shown as seen from the Cassini-Huygens space probe.) 3. The thin blue line (The third episode looks at the planets of the Solar System, with Earth Mars, and Titan being the main focus. The episode starts Cox taking a journey up to 60,000 feet in an English Electric Lightning. Later, the Namib Desert is seen and used to give an explanation on how the Earth keeps its temperature, along with comparisons made to Mars. An in-depth look at Titan is seen with footage shown from the Huygens probe descent down to the surface of the moon.